Investigating the electronic properties and reactivity of polyaniline emeraldine base functionalized with metal oxides - Rania Badry; Hanan Elhaes; Asmaa Ibrahim; Ahmed Refaat; Medhat A. Ibrahim (Scientific Reports)
Abstract Due to its appealing qualities, such as its miniature size and the ability to modify physical properties through chemical synthesis and molecular design, polymer material offers considerable advantages over traditional inorganic material-based electronics. Conjugate polymers are particularly interesting because of their molecular design capabilities, which enable the synthesis of conducting polymers with a variety of ionization potentials and electron affinities (EA), and their ability to control the energy gap and electronegativity (χ). Accordingly, density functional theory (DFT) at the B3LYP/SDD model was used to present possible interactions between polyaniline (PANi) and both alkali and heavy metal oxides. Total dipole moment (TDM), HOMO–LUMO band gap energy (ΔE), ionization energy (IE), EA, chemical hardness (η), chemical potential (μ), electrophilicity index (ω), chemical softness (S), and χ are calculated. TDM of PANi increased while ΔE decreased due to functionalization. The distribution of electronic charge density in molecular electrostatic potential (MESP) maps together with the results of ω reflected the electrophilic nature. The obtained results confirmed that the addition of metal oxides significantly improves the TDM, ΔE, and reactivity descriptors. A strong correlation between the experimental and calculated IR spectra was observed. Additionally, PANi–2MgO and PANi–2MnO model molecules exhibited the highest reactivity. Accordingly, PANi functionalized with MgO and MnO are promising candidates for energy storage devices.